Elementary Chinese level 1 - Poey, Tiang Peow (August Publishing Sdn Bhd, 2015)
It is a well-crafted book for the begineers of Mandarin Language where all the relevant lessons are covered. The book has been divided into fourteen lessons, and each part is self-contained yet they are interrelated. The book can be a great advantage of reference for people who wish to travel and interact with Chinese dominated areas.